He was a quiet man [videorecording (DVD)] - Cappello, Frank; Slater, Christian; Cuthbert, Elisha; Macy, William H., 1950-; Knopf, Sascha; Gulager, John (Anchor Bay Entertainment, 2008)
"Bob Maconel [is] a bullied office drone with hate in his heart, voices in his head, and a loaded gun in his desk drawer. When a bizarre twist turns him into an instant hero, Bob begins a tender relationship with a disabled co-worker who asks Bob for the ultimate favor."--Container.